Guía metodológica para evaluar la toma de conciencia de los sistemas de gestión ambiental y seguridad y salud en el trabajo (2015)
"Bearing in mind that workplace accidents are a source of hardship and suffering for workers and their families, environmental damage and significant economic loss to the community, it is necessary to determine the factors that influence their occurrence; Studies have shown that the frequency and severity of accidents depend on the inherent dangers of work and physical, physiological and psychological factors of the worker, which leads to conclude that injuries are largely caused by lack of awareness of the same workers (ILO, 2015) In line with the above, according to the ILO, in its article on Safety and Health at Work, it says that every 15 seconds a worker dies because of work-related accidents or illnesses; every 15 seconds 160 workers have an accident at work; every day 6,300 people die from work-related accidents or illnesses, more than 2.3 million deaths per year almost double the deaths caused by the war and more than those that malaria is charged with; Every year more than 317 million accidents occur at work, many of these accidents result in absenteeism. The cost of this daily adversity is enormous and the economic burden of poor safety and health practices is estimated at 4% of the global gross domestic product of each year. (Mintrabajo, 2014) "- Excerpt from the text